Micro Nutrients (Fe, Mn, Zn, and pH) Effluent Digester Biogas Raw Material Water Hyacinth (Eichornia crassipes) as Raw Material for Organic Fertilizer - Hery Koesmantoro; Karno Karno; Sunaryo Sunaryo (Alliance oh Health Activists (AloHA), 2021)
Introduction: Water hyacinth (Eichhornia crassipes) which has the ability to grow very fast has turned into wild aquatic plants and causes losses, among others, accelerates silting of waters, reduces fish production due to taking up space and nutrients that are also needed by fish, complicating irrigation channels, blocking boat traffic and causes greater evaporation of water than in open water. The research objectives were: To utilize the effluent digester of biogas as raw material for water hyacinth (Eichhornia crassipes) as a liquid organic fertilizer by analyzing macro and micro nutrients. Methods: The study design was one group post test design. The research was conducted by taking samples in Bening Reservoir (PT.Jasa Tirta): Pajar Village, Saradan District, Madiun Regency, East Java. The research was carried out in the Laboratory of D-III Environmental Health Magetan Poltekkes of the Ministry of Health, Surabaya and the Laboratory of Soil Science, Faculty of Agriculture, Sebelas Maret University, Surakarta. The research was carried out with treatment for: 7 days, 14 days and 21 days by measuring: Micro nutrient elements. set and the pH at the end of the observation. Treatment activities and variations in research dosages were as follows: The number of research samples was: 6 samples with research parameters for micro nutrients: Fe, Mn, Zn and pH. The sampling technique was simple random sampling. Tools used: A set of fermentation tools in the form of a bucket with a lid equipped with a wooden stirrer, measuring cup and scale. The research materials include: biogas effluent digester (raw material for fertilizer), fermentation bacteria / fermenter (EM-4), molasses and water. Data were collected by conducting laboratory examinations of samples sent and examined with micro nutrient parameters according to variations in observation time. Data analysis was carried out by comparing the requirements for organic fertilizers. Minimum Technical Requirements for Organic Fertilizer, Biofertilizer and Soil Improvement. All micro nutrient parameters (Fe, Mn, Zn and pH) are in accordance with the required standards for fertilizers. Results: Micro nutrients (Fe): 192 ppm, without treatment as a control decreased to: 66.86 ppm, Mn nutrients, without treatment: 119.46 ppm, Zn analysis results, without treatment: 9.92 ppm, pH parameters have met the requirements, namely between 4-9 while the results of laboratory tests are in the range of 6.96 - 7.93. The results of the research on the treatment with the addition of EM-4 & Molasses with fermentation time of 7, 14 and 21 days, there was a decrease in the quality of micro nutrients, not according to the quality standards of liquid fertilizers. Conclusion: The conclusion of the results of this study is that the micro nutrient content before treatment (Fe, Mn, Zn) and pH, it turns out that some have met the requirements according to the Ministry of Agriculture, except that Zn nutrients are still below the standard. Micro nutrient content after treatment week 1 to week 3 and control, the nutrients (Fe, Mn, Zn) and pH were still below without treatment. The effluent of the biogas digester as raw material for water hyacinth without any treatment has met the requirements as an organic fertilizer as long as its use has exceeded 60 days in the digester. Keywords: water hyacinth; biogas energy; micro nutrients; organic fertilizers